A origem da violência nas aulas de educação física : a prática pedagógica do professor - Mello, Tiago Lepre (Universidade Federal de São Carlos, 2016)
Violence is a historical and cultural phenomenon present in human social relations in all dimensions of society. The school is not immune to the influences of society and the violence invades the school environment becoming frequent in its daily routine. The teacher's pedagogic practice is responsible for the educational and relational process that happens in class and, consequently, has a responsibility in the creation of violence manifestations, which may hamper the development of teaching and put at risk the student’s integrity. In order to contribute to discussions related to the teacher's work (teaching methodology, content, pedagogical intervention, teacher-student relationship, professional attitude, commitment to the profession, and so forth), the overall objective of the research was to identify, analyze and discuss the origin of violence in Physical Education classes, and specific objectives have been identified the types of violence manifested in classes and situat ions cause that gave rise to it, analyzing aspects of teaching practice of Physical Education teacher who present relationship with the origin and development of situations cause for violence. The research was conducted with two groups of 5th year primary school students, during Physical Education classes of two municipal public schools in Porto Ferreira/São Paulo, Brazil. In research methodology, we used a qualitative approach to the descriptive explanatory type, and the data collection was done through the following methodological tools: diary, in which data from thirty-seven lessons observed were noted; semi-structured interview with the two Physical Education teachers; questionnaire with students; and analysis of the Pedagogical Political Project of both schools. Based on data analysis, it was identified that the pedagogical practices licentious and teacher’s authoritarianism enables the establishment of environments conducive to the emergence of nine situations cause of violence: physical contact group activity; match error; sum game; game rule; exclusion; idleness; unfriendly relationship between teacher and student; punitive practice; and the exercise of teaching authoritarianism. Such situations triggered physical, verbal, psychological and disruptive violence manifestations among school components. It considers in this clipping, that the licentious and authoritarian practices developed by the teacher relates to the promotion of spaces for social interaction susceptible to the emergence of conflict situations, which allow the students to express their violent behavior in Physical Education classes.
Keywords: Violência escolar; Prática pedagógica; Professor; Educação física; School Violence; Physical Education; Teaching Practice; CIENCIAS HUMANAS::EDUCACAO::CURRICULO